Evaluation of Drug Management Achievement in Pharmacy Installation of Langsa General Hospital - M, Mauliana; W, Wiryanto; Harahap, Urip (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: to evaluate the achievements of drug management in Pharmacy Installation of Langsa General Hospital Design: The study used descriptive designs for 2018 data which were retrospective and prospective. Data was collected in the form of quantitative and qualitative data from document observations and interviews with relevant Pharmacy Installation officers. Interventions: the intervened variable were drug selection, planning and procurement, and distribution. Main outcome measures: the main measurement in this study were suitability of drug items available with the National Formulary, frequency of procurement of each drug item per year, accuracy of data on the number of drugs on the stock card, percentage and value of expired and / or damaged drugs, percentage of dead stock and level of drug availability. Results: drug management system that conformed to the following standards were the suitability of the available drug items with the National Formulary (88.37%); the accuracy of data on the number of drugs on the stock card (100%) and drug availability (13 months 14 days). Drug mangement which were not accordance with standard: the frequency of procurement of each drug item per year; percentage of expired and / damaged drug values (2.64%) and percentage of dead stock (3.24%). Conclusion: it could be concluded that the management of drugs in Langsa General Hospital Pharmacy Installation had not been fully effective and efficient in accordance with established standards.